Revitalization of Kali Unda Tourism Objects - Nataprawira, Muhammad Rafli Ramdhani; Yudha, I Made Bendi; Gulendra, I Wayan (PROGRAM STUDI SENI MURNI ISI DENPASAR, 2023)
Paksebali Village is one of 12 villages in Dawan District and is located east of Semarapura City, 1 Km away. Paksebali Village consists of 5 Office Banjars. The Klungkung River Dam Tourism Object, which is currently called the Unda River Tourism Object, is the most easily accessible tourist attraction because when heading to this area it is located close to the connecting bridge between Klungkung City and Dawan District. The Kali Unda Tourism Object has a natural panorama that captivates tourists because this tourist spot has a dam that forms a two-story waterfall, which is known as